Factor X Deficiency: A Rare Case of Inherited Coagulation Disorder Presenting As Hemarthrosis - Sweta Sinha; Sumit Barik (International Journal of Medical Research and Review, 2014)
Hemophilia due to factor VIII deficiency is most common inherited bleeding disorder in paediatric population. Hemarthrosis is initial manifestation in large number of patients. We are presenting a case of factor X deficiency who presented with knee hemarthrosis.